Clinical Implications of Phenotypes of Hemodialysis Patients With Central Venous Occlusion or Central Venous Stenosis Defined by Cluster Analysis - Wen, Chunyong; Chen, Bin; Lin, Run; Dai, Haitao; Tang, Keyu; Zhang, Guiyuan; Huang, Jiawen; Liao, Changli; Zeng, Linyuan; Xiang, Xianhong; Yang, Jianyong; Huang, Yonghui (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aims to investigate the association between clinical factors of patients with CVO/ CVS and the difficulty of interventional recanalization as well as the duration of postoperative patency. Methods: A total of 103 hemodialysis patients with CVO/ CVS treated with endovascular treatment were enrolled. The two-step cluster analysis was selected to differentiate the cases into distinct phenotypes automatically. Differences in characteristics, the difficulty of interventional recanalization, and the duration of postoperative primary patency time between the two clusters were statistically compared. Results: The 103 cases were divided into distinct 2 clusters by the two-step cluster analysis with 48 (46.6%) in cluster 1 and 55 (53.4%) in cluster 2. Compared to cluster 2, patients in cluster 1 have a higher proportion of blunt stump, side branches, occlusion lesions >2 cm, calcification, or organization. Moreover, the above four factors were, in turn, the most critical four predictors distinguishing 103 patients into 2 clusters. The remaining six factors were, in turn, occlusion located in SVC, duration of CVC, lesion location, vessel diameter, number of CVC, and previously failed lesion. The operation time of cluster 1 was longer than that of cluster 2. In terms of postoperative patency time, the primary patency time was significantly longer in the patients of cluster 2 compared with cluster 1 (P=0.025). Conclusion: Patients were divided into distinct 2 clusters. CVO/ CVS of patients in cluster 1 were more challenging to be recanalized than that in cluster 2 and the primary patency time was significantly longer in the patients of cluster 2 compared with cluster 1. Blunt stump, side branches, occlusion lesions exceeding 2cm, calcification or organization are the most critical predictors distinguishing 103 patients into 2 clusters.